FCFS-R5-067: Management of Knowledge Transfer Programme on Good Aquaculture Practices to Seabass Cage Culture Farmers in Tumpat, Kelantan - Bee Lee Ong; Tan Li Peng; Ruhil Hayati Hamdan; Suhaily Suhana Mohd Yusoff; Haji Yusoff Che Mamat (2016)
Seabass brackish water cage culture is a very profitable and challenging enterprise. However, the main problem of the culture is high mortality of fish due to factors such as improper management, water quality, environmental and diseases. The fish farming community in Laguna Sri Tujuh, Tumpat, Kelantan, has been continuously facing poor production of seabass due to high mortality of fish (fish kill) and poor aquaculture practices among fish farmers since the start of the cage culture in 2003. Knowledge transfer programme on good aquaculture practices (GAP) was initiated and undertaken by a group of researchers from Universiti Malaysia Kelantan (UMK) in January, 2016. Knowledge on GAP was transferred to the community through onsite training by using the Department of Fisheries (DOF) Malaysia seabass cage culture cluster project site as a model for this community. Guidance on water quality monitoring and methods on improving water quality were demonstrated. Important records such as daily mortality rate, feed consumption, fish stocks, and water physical properties were established. The farmers were taught on proper way of grading fish, feed and feeding management, proper waste disposal, prudent use of drugs, and use of immune enhancers as preventive medicine. In addition, Faculty of Veterinary Medicine, UMK also provides fish disease diagnostic services to the fish farmers. It is envisage that the seabass cage culture farmers who participated in this programme will be able to improve their production and raised their income by reducing fish mortality. The programme also aims to strengthen collaboration among fish farming community, DOF’s authority and researchers of UMK in promoting GAP for sustainable and profitable aquaculture. The programme will also produce a competent graduate intern with knowledge and technical skills in the brackish water cage culture, enhancing her employability in the aquaculture sector